2015
DOI: 10.5812/pedinfect.30084v2
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Hydatid Disease in Iranian Children

Abstract: Background: Hydatid disease (HD) is still an important health hazard in the world. This disease is a parasitic infestation endemic in many sheep-and cattle-raising areas such as Iran. Objectives: This study aimed to review the clinical manifestations, laboratory aspects, imaging findings, and management of HD. Patients and Methods: Data were collected from the medical records of patients diagnosed with HD in eight referral hospitals in different provinces of Iran from 2001 to 2014. Results: Overall, 161 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
6
5
1
Order By: Relevance
“…Boys, more so than girls, are considered to be closer canine companions and may be more at risk to potential zoonotic infection through the faecal-oral route during the course of feeding, working or playing with their dogs. The results of this study corroborate those previously reported in other paediatric studies quoting that boys are more likely to be infected than girls, with male to female ratios ranging from 1.3:1 to 2.1:1 (Wang et al 2001;Durakbasa et al 2006;Fahimzad et al 2015). In contrast, a predominance of CE in females has been reported (Pierangeli et al 2007;Sanaei Dashti et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Boys, more so than girls, are considered to be closer canine companions and may be more at risk to potential zoonotic infection through the faecal-oral route during the course of feeding, working or playing with their dogs. The results of this study corroborate those previously reported in other paediatric studies quoting that boys are more likely to be infected than girls, with male to female ratios ranging from 1.3:1 to 2.1:1 (Wang et al 2001;Durakbasa et al 2006;Fahimzad et al 2015). In contrast, a predominance of CE in females has been reported (Pierangeli et al 2007;Sanaei Dashti et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This study indicates that the lung is the most common site of CE in children , similar to other pediatric data [4,5] . Pulmonary cysts grow slowly and are often asymptomatic until complications such as mass effect, rupture or secondary infection, occur [21] .…”
Section: Discussionsupporting
confidence: 91%
“…Unlike adults, where hepatic involvement is common, pulmonary CE is the dominant site in the pediatric population [4] . Pulmonary cyst/s are typically first seen on chest x-ray (CXR), either as an incidental finding or following respiratory symptoms after cyst rupture or secondary infection of the cyst [5] . Pulmonary cysts have a broad differential diagnosis in children and a definitive diagnosis relies on the combination of imaging, serology, and histology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney-sparing surgery and cystectomy plus pericystectomy are feasible in 75% of cases and total nephrectomy must be performed for nonfunctional kidneys (2,5,8,12,13).…”
Section: Discussionmentioning
confidence: 99%